TEI Critical Apparatus Toolbox: Web-based tools for ongoing XML-TEI editions - Bastien Dumont (RIDE, 2022)
Despite the flexibility that a TEI-based workflow offers for preparing editions based on collating several manuscripts, textual scholars working with XML-TEI edition files face a lack of domain-specific auxiliary tools. The TEI-CAT partially fills this gap by providing interfaces for visualizing the transcription of different manuscripts and for exploring the encoded variations and detecting common mistakes. While not properly supporting several types of textual variation and editorial intervention, these tools satisfy most of the needs usually arising during transcription and collation. The image annotation tool complements them by allowing users to generate TEI-compliant code. This tool very flexibly describes or comments on facsimile layout and content and thus is particularly helpful in preparing digital editions. Finally, the PDF-via-LaTeX exporting facility extends the scope of the toolbox towards traditional paper-based publishing, which often remains an editor’s ultimate goal. However, this tool requires adopting specific encoding practices, which are not made explicit and may not match the user’s choices; its output needs manual modifications in some cases. Together, these tools partially illustrate how the XML-TEI format can be used to prepare critical editions. They constitute an important step towards creating a TEI-based digital environment in this field.